Islamic Boarding Schools as Learning Organizations: Integrating Tradition and Digital Innovation in Student Leadership Development - Hermanto Halil (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the integration of pesantren tradition, managerial innovation, and external collaboration as a model for strengthening santri leadership capacity in Indonesia. Pesantren, as traditional Islamic educational institutions, play a central role in shaping future leaders grounded in religious values. However, the challenges of modernization, globalization, and digital transformation require pesantren to adapt without losing their authenticity. The purpose of this research is to analyze how leadership education in pesantren can develop through the synergy of traditional values, technological innovation, and strategic partnerships. The research employed a qualitative approach through participatory observation and in-depth interviews with pesantren leaders, santri, and external stakeholders. The findings reveal that the integration of tradition, digital managerial innovation, and external collaboration are strategic factors in strengthening santri leadership capacity within pesantren. Tradition continues to serve as a moral and spiritual foundation instilling honesty, responsibility, and the exemplary role of the kiai. Meanwhile, technology-based managerial innovation brings transformative change through digital administration, learning management systems, and online communication applications that foster participatory and adaptive leadership. Furthermore, collaboration with government, NGOs, and the private sector enriches santri leadership experiences through practical training beyond the religious sphere.